Seismic behaviour of damaged tunnel during aftershock. (November 2018) - Singh, D.K.; Mandal, A.; Karumanchi, S.R.; Murmu, A.; Sivakumar, N.
Abstract: This paper studies the seismic behaviour of tunnels that are damaged during aftershocks. The tunnels were made from three different materials that had different flexural rigidity. An undamaged tunnel was constructed out of one material, while the damaged tunnels were built with the other two materials. The seismic load was applied with a unidirectional shake table. The peak ground acceleration for various input motions varied from 0.1 g to 1.2 g. The dynamic earth pressure around the tunnel was measured using three soil pressure transducers. The tunnel was placed in the transverse direction of shake table motion. The properties of the surrounding soils were calculated from bender element. The peak dynamic stress generated in the soil was used to study the behaviour of the damaged tunnels. A hand-held vibration analyser was used to measure the motion of the shake table. The results show that the damaged tunnel is more vulnerable to low frequency seismic motion. Highlights: Damaged tunnel behavior during aftershock is studied. Low frequency aftershock is riskier to damaged tunnel. Predominant frequencies reduces for damaged tunnel.